2014
DOI: 10.1093/infdis/jiu017
|View full text |Cite
|
Sign up to set email alerts
|

Voriconazole Metabolism, Toxicity, and the Effect of Cytochrome P450 2C19 Genotype

Abstract: CYP2C19 and 2C9 genotypes were not major determinants of voriconazole metabolism. No toxic serum level of voriconazole or its metabolites could be identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(119 citation statements)
references
References 20 publications
3
110
1
Order By: Relevance
“…In the present study, we found that the minor allele frequency of CYP2C9*2 and CYP2C9*3 SNPs in our population was very low, in accordance with that seen in the Chinese Han population through the HapMap database. This can also be interpreted as the *2 and *3 SNPs not affecting the plasma voriconazole concentration in the Chinese population, in accordance with the findings of the three aforementioned studies [13,18,27]. No effect was found for the other SNPs of CYP2C9.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, we found that the minor allele frequency of CYP2C9*2 and CYP2C9*3 SNPs in our population was very low, in accordance with that seen in the Chinese Han population through the HapMap database. This can also be interpreted as the *2 and *3 SNPs not affecting the plasma voriconazole concentration in the Chinese population, in accordance with the findings of the three aforementioned studies [13,18,27]. No effect was found for the other SNPs of CYP2C9.…”
Section: Discussionsupporting
confidence: 90%
“…While there are few published controlled clinical trials regarding the influence of different CYP2C9 genotypes on the pharmacokinetics and metabolism of voriconazole, there have been some indications that the CYP2C9 genotype might not be relevant to voriconazole pharmacokinetics. One study found no effect of the CYP2C9 genotype on voriconazole levels [27]. Furthermore, a case report found that the voriconazole pharmacokinetics of a patient who was homozygous for CYP2C9*2 were unchanged [18].…”
Section: Discussionmentioning
confidence: 99%
“…Most reports have been in children, with incidence reported to be as high as 20% [55], and 10.5% in patients aged over 12 years [56]. However, neither study was specific to patients who had received alloHSCT.…”
Section: Adverse Eventsmentioning
confidence: 99%
“…At present, the relationship between voriconazole concentrations and toxicity is not well understood [60,121].…”
Section: Safetymentioning
confidence: 99%
“…CYP2C19 represents about 1% and CYP3A4 approximately 30% of the total hepatic complement [182]. To varying degrees, voriconazole is an inhibitor and/or substrate of CYPs 2B6, 2C19, 2C9, and 3A4 [9,164,183,184] with CYP2C19 playing the predominant, but not exclusive role in voriconazole's metabolism [121,185,186]. Genetic variation in CYP2C19 that limits metabolic activity may influence the potential for DDIs [18,58,187].…”
Section: Drug-drug Interactionsmentioning
confidence: 99%